Input-Output Analysis: Which Tax Incentive for Natural Resources Downstream Is Suitable for Indonesian Economy? - Destiny Wulandari (Ilomata International Journal of Tax and Accounting, 2023)
Indonesian government's policy to promote downstream natural resources leads to tax incentives policy intended to encourage the downstream. This study focuses on corporate income tax incentives in the form of net income reduction (tax allowance according to Article 31A of the Income Tax Law) by 30 percent for 6 years or corporate income tax reduction (tax holiday according to Minister of Finance Regulation Number 130/PMK.010 /2020) by 100 percent or 50 percent. Despite the positive or negative impact of tax incentives enactment argued in the previous studies, this study will calculate the impact on the economy provided by the mentioned tax incentive schemes quantitatively and will analyze which tax incentive scheme gives the greater impact on the economy. The analysis was carried out by using input-output analysis method to calculate the impact from output approach on secondary data in the form of the latest input output table released by Badan Pusat Statistik i.e., 2016 input output table. The result of the study shows that tax incentive in the form of tax holiday with income tax reduction by 100 percent provides greater impact on the economy than the others do. The total impact is getting greater and shows comparable results as the tax incentive rate increases. However, the result of this study implies that the implementation of tax incentives still needs the right tax incentive policy design to gain the expected results.